A toast to murder - Abbott, Allyson K. (Abbott, Allyson K. Mack's Bar mystery., 2017)
As Milwaukee counts down to New Year's Eve, bar owner Mackenzie "Mack" Dalton has but one resolution--unmask the dangerous mastermind who has been taunting her and killed bouncer Gary Gunderson. Mack and her fellow barflies have fleshed out a suspect and arranged an invite-only party to put a cork in the murderer's game for good. But when the clock strikes midnight and their suspect is found cold and stiff on the basement stairs, it seems the celebration may have come too soon. Now Mack must rely on her special talents to find the real criminal among the crowd of revelers--or someone won't survive until last call ...